Public Knowledge About Emergency Care—Results of a Population Survey From Germany - von dem Knesebeck, Olaf; Koens, Sarah; Schäfer, Ingmar; Strauß, Annette; Klein, Jens (Frontiers in Public Health, 2022)
Background: Knowledge and beliefs about health and health care are part of the general concept of health literacy. Studies demonstrated that large parts of the population report inadequate health literacy. There are only few studies specifically addressing public knowledge and beliefs about emergency care. We examine magnitude and social variations of public knowledge about emergency care in Germany. Methods: Analyses make use of a telephone survey conducted in Hamburg, Germany. Random sample consisted of 1,207 adult respondents. We asked whether the respondents know various emergency care services. Moreover, capabilities of dealing with an emergency case were assessed. Sex, age, education, and migration background were introduced as predictors into regression models. Results: 98% of the respondents stated to know the rescue service, while 74% knew the medical on call service and 49% were aware of an emergency practice nearby. About 71% of the interviewees said it was easy for them to find out whom to turn to in a case of a medical emergency. Fewer respondents found it easy to evaluate when to use emergency medical services and to evaluate whether a health problem is a medical emergency. Knowledge and capabilities were positively associated with education and negatively related to migration background. Conclusions: This study indicates a lack of public knowledge about emergency care and social inequalities in public knowledge according to education and migration status. Findings suggest that interventions are needed to improve public knowledge and that considering social inequalities should be a basic principle for such interventions.